1998
DOI: 10.1093/jnci/90.3.210
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of Cognitive Function in Women Receiving Adjuvant Treatment for High-Risk Breast Cancer: High-Dose Versus Standard-Dose Chemotherapy

Abstract: High-dose chemotherapy appears to impair cognitive functioning more than standard-dose chemotherapy. Central nervous system toxicity may be a dose-limiting factor in high-dose chemotherapy regimens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
470
9
17

Year Published

1999
1999
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 694 publications
(522 citation statements)
references
References 27 publications
26
470
9
17
Order By: Relevance
“…A second long-term toxicity that we have recently described is impairment of cognitive function (van Dam et al, 1998). This type of toxicity has been associated with a single high-dose course CTC and many of the patients reported here have contributed to these studies (Schagen et al, 2001).…”
Section: Discussionmentioning
confidence: 61%
“…A second long-term toxicity that we have recently described is impairment of cognitive function (van Dam et al, 1998). This type of toxicity has been associated with a single high-dose course CTC and many of the patients reported here have contributed to these studies (Schagen et al, 2001).…”
Section: Discussionmentioning
confidence: 61%
“…The 95th percentile of the healthy controls was used as a cutoff score for cognitive disability. 25 The application of this algorithm to our data showed that a glioma patient was judged to have a cognitive disability if he or she had deviant scores for at least four of the 20 tests. Only tests for which healthy controls could be individually matched with low-grade glioma patients for age, sex, and educational level were used for this analysis.…”
Section: Study Measuresmentioning
confidence: 90%
“…29 We saw a somewhat stronger relation between objective test results and self-reported cognitive function than that noted in earlier studies of patients with brain tumours and those with systemic cancer. 25,30 Cull and colleagues 17 suggested that cognitive complaints of cancer patients might actually indicate feelings of anxiety, depression, or fatigue. Moreover, a dissociation between objective cognitive test results and self-reported cognitive function holds true especially for patients with brain cancer whose judgment could be severely impaired by the tumour.…”
Section: Patient Groupsmentioning
confidence: 99%
“…Cyclophosphamide; Doxorubicin; Chemotherapy; Learning; Rat A growing body of evidence indicates that cancer chemotherapy results in cognitive changes during treatment, immediately post-treatment, and up to 10 years following therapy [2,4,15,21,25,32]. The cognitive deficits that are experienced are diverse and vary in severity; however, problems with memory function and executive processes are the most…”
Section: Introductionmentioning
confidence: 99%